1997
DOI: 10.1002/food.19970410407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lupine flour on the quality and oligosaccharides of pasta and crisps

Abstract: In this study the nutritional value and customer acceptance of pasta and crisps produced with addition of 5, 10 and 15% of lupine flours (L. luteus, L. albus, L. angustifolius) were evaluated.Pasta and crisps were tested on the basis of organoleptic and physicochemical analysis. The contents of oligosaccharides as well as protein, its digestibility and amino acids components, lipids and alkaloids were analysed.The amount of oligosaccharides in raw pasta with lupine flour, contrary to crisps, was much lower tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…The EAA, Val, sulphur amino acids, Lys and Thr content were below standard values, while His, Ile, Leu, aromatic amino acids and Trp were higher or close to the referred standards. The NEAA and EAA contents of cooked semolina pasta are in agreement with findings reported in the literature (Bergman, Gualberto, & Weber, 1996;Lampart-Szczapa, Obuchowski, Czaczyk, Pastuszwewska, & Buraczewska, 1997;Abdel-Aal & Hucl, 2002;Shogren, Hareland, & Wu, 2006), except for an apparent discrepancy in the Pro values (10-11 g/16 g N) reported by other authors (Lampart-Szczapa et al, 1997;Shogren et al, 2006). Genotypic differences may explain the variations between Pro values reported here and the literature (Anjum, Ahmad, Butt, Sheikh, & Pasha, 2005).…”
Section: Amino Acid Composition and Cs Of Fermented And Germinated Pisupporting
confidence: 92%
“…The EAA, Val, sulphur amino acids, Lys and Thr content were below standard values, while His, Ile, Leu, aromatic amino acids and Trp were higher or close to the referred standards. The NEAA and EAA contents of cooked semolina pasta are in agreement with findings reported in the literature (Bergman, Gualberto, & Weber, 1996;Lampart-Szczapa, Obuchowski, Czaczyk, Pastuszwewska, & Buraczewska, 1997;Abdel-Aal & Hucl, 2002;Shogren, Hareland, & Wu, 2006), except for an apparent discrepancy in the Pro values (10-11 g/16 g N) reported by other authors (Lampart-Szczapa et al, 1997;Shogren et al, 2006). Genotypic differences may explain the variations between Pro values reported here and the literature (Anjum, Ahmad, Butt, Sheikh, & Pasha, 2005).…”
Section: Amino Acid Composition and Cs Of Fermented And Germinated Pisupporting
confidence: 92%
“…Scarce data concerning the content of pigments in leguminous plants can be found in the literature. Daood et al [22] found 0.22 mg beta-carotene in 100 g fresh matter of the common pea and Lampart-Szczapa [23] 0.02-0.14 mg in lupin seeds. Souci et al [24] reported the following content of beta-carotene in 100 g dry seeds: 0.32 mg in the soyabean, 0.18 mg in the chickpea, and 0.10 mg each in the common pea and lentil.…”
Section: Resultsmentioning
confidence: 99%
“…Durum wheat semolina can be fortified with legume flours to enhance their nutritional properties. 8 LampertSzczapa et al 33 have supplemented pastas with lupin up to 150 g kg −1 and observed that the pasta products contain high amounts of flatulent oligosaccharides. Hall and Johnson 6 fortified pasta with lupin up to 190 g kg −1 and palatability studies showed that the general acceptability of supplemented pasta was lower than the control, although the protein and fat content increased.…”
Section: Discussionmentioning
confidence: 99%